"DISTRIBUTED PROCESSING MODELS AND ALGORITHMS OF SENSOR DATA" - Annazarova Barno Rustamovna; Otajonova Gulhayo Maqsud’s Daughter; Madirimova Saodatjon Madirimovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, models and algorithms for distributed processing of Sensor data were extensively covered. Wireless sensors and sensor platforms have been revealed.